Predictive value of proteinuria in adult dengue severity. - Farhad F Vasanwala; Tun-Linn Thein; Yee-Sin Leo; Victor C Gan; Ying Hao; Linda K Lee; David C Lye (Public Library of Science (PLoS), 2014)
BACKGROUND: Dengue is an important viral infection with different presentations. Predicting disease severity is important in triaging patients requiring hospital care. We aim to study the value of proteinuria in predicting the development of dengue hemorrhagic fever (DHF), utility of urine dipstick test as a rapid prognostic tool. METHODOLOGY AND PRINCIPAL FINDINGS: Adult patients with undifferentiated fever (n = 293) were prospectively enrolled at the Infectious Disease Research Clinic at Tan Tock Seng Hospital, Singapore from January to August 2012. Dengue infection was confirmed in 168 (57%) by dengue RT-PCR or NS1 antigen detection. Dengue cases had median fever duration of 6 days at enrollment. DHF was diagnosed in 34 cases according to the WHO 1997 guideline. Dengue fever (DF) patients were predominantly younger and were mostly seen in the outpatient setting with higher platelet level. Compared to DF, DHF cases had significantly higher peak urine protein creatinine ratio (UPCR) during clinical course (26 vs. 40 mg/mmol; p<0.001). We obtained a UPCR cut-off value of 29 mg/mmol based on maximum AUC in ROC curves of peak UPCR for DF versus DHF, corresponding to 76% sensitivity and 60% specificity. Multivariate analysis with other readily available clinical and laboratory variables increased the AUC to 0.91 with 92% sensitivity and 80% specificity. Neither urine dipstick at initial presentation nor peak urine dipstick value during the entire illness was able to discriminate between DF and DHF. CONCLUSIONS: Proteinuria measured by a laboratory-based UPCR test may be sensitive and specific in prognosticating adult dengue patients.